Hurried to Destruction: Reprobation in Arden of Faversham and A Woman Killed with Kindness - Clark, Glenn (Renaissance and Reformation / Renaissance et Réforme, 2018)
This essay demonstrates that Arden of Faversham and A Woman Killed with Kindness explore important tensions in the Elizabethan understanding of the lived experience of the damned. Calvinist theologians tended to describe reprobation in terms that unintentionally suggested direct divine agency and responsibility, despite their insistence that culpability for sin lies in human nature. Aligning closely with Calvinist visions of reprobation, the plays characterize their villains as feeling compulsions to sin so powerful that they are experienced as external impositions, even as these characters presume their own internal sinfulness. The agonizing inescapability of these characters’ compulsions is emphasized through contrast with the ambiguous liberations of the plays’ female protagonists. The plays highlight the contradiction in Calvinist descriptions of reprobation by generating dramatic effects that prompt audiences to suspect that what the tortured reprobates experience as divine interference is real rather than merely a projection of guilt. Despite their Calvinist elements, the plays reinforce the doubts raised by anti-Calvinists about English Calvinism’s predestinarian theology.